The Leadership Role Of School Principals In Setting The Direction To Develop Resilience In Schools - Yuda Saputra, Handika; Hidayati, Dian (Universitas Ahmad Dahlan, 2024)
This research was motivated by the school's situation in developing school resilience by setting the direction of school practice. The purpose of this study was to analyze and describe the leadership practices of principals in setting the direction extensively to improve school resilience. This study used qualitative research through data collection, such as observation and interview techniques with four informants, and documentation with data analysis techniques employing description, analysis, and interpretation. The findings of this study suggest that by performing the principal leadership role, namely setting the direction, a school could develop resilience adequately.